Durham University students’ experiences of asymptomatic COVID-19 testing: a qualitative study - Leah Ffion Jones; Jo Taylor; Dale Weston; Eleonore Batteux; Stefanie Bonfield; Jaskiran Kaur Bhogal; Camila Caiado; Jacqui Ramagge (BMJ Open)
Objectives To evaluate the asymptomatic coronavirus testing programme at Durham University by exploring students’ barriers and facilitators to taking part and provide recommendations to improve the programme.Design Qualitative interviews.Setting Online.Participants 30 students enrolled at Durham University were interviewed in March 2021.Main outcome measures Attitudes towards testing, experiences of testing and barriers and facilitators to engaging in testing at Durham University.Results Key motivations for testing included protecting oneself and others and accessing facilities and events. The process of booking, accessing and doing a test was mostly easy and convenient, although some may prefer home testing. There were concerns about the accuracy of tests and the implications of a positive result. Some highlighted they might be less likely to engage in testing if vaccinated. A negative test result provided confidence to engage in their daily activities, while encouraging some to socialise more.Conclusions The findings show that the testing programme at Durham University is convenient and well organised, with testing as a potential requirement to access social events, and self-isolation support being key contributor to uptake. These findings provide insights into young adults’ attitudes towards testing and can inform testing programmes in other universities and settings with asymptomatic testing programmes.